The Analysis of Plot in â€œSnow White and the Seven Dwarfsâ€ Story by Vera Southgate and Disney â€œSnow White and the Seven Dwarfsâ€ by Using Formalism Approach - Luh Rista Hardiantini (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This research aims to analyze the intrinsic element: it is the plot in the story "Snow White and the Seven Dwarfs" by Vera Southgate and Disney â€œSnow White and the Seven Dwarfsâ€ film adaptation by employing a formalistic or formalism approach. Analyzing the plot in story and film is done by reading the text and understanding the plot structure that was adapted by the author. Story and film use particular terms in their plot selection. In analyzing the element, the author started by determining the segmentation of the story and find out the plot structures that were built. Based on the data generated and supported by the experts, there is a relationship between plot development and the existence of Disney's works among film enthusiasts. Disney's work became phenomenal due to the plot presented by the author. Both story and film are packed with neat stories and provide the readers with an overview and knowledge of life.